DOP67 A transcriptional module associated with neutrophil degranulation is highly conserved across species and is a core molecular pathway of treatment resistance in ulcerative colitis. (30th January 2023) - Cozzetto, D; Lo, J; Powell, N
Abstract: Background: Advanced therapeutics are changing the treatment landscape in ulcerative colitis (UC), but drug resistance is still common. New strategies are needed to identify the molecular and cellular drivers of treatment resistance and inform the development of novel molecular diagnostics and therapies. In this study we analysed transcriptional modules conserved across species and different colitis models to look for fundamentally important pathways of disease. Methods: We surveyed the colonic transcriptome in preclinical UC models, including the T-cell transfer, Il10-/ -, DSS, DNBS, anti-CD40 mAb and TRUC ( Tbx21-/- x Rag2-/ - UC) models and multiple cohorts of patients with UC. Gene expression and pathway level changes were defined. Conserved gene and pathway level changes were defined and their relationship to treatment response with anti-TNF, ustekinumab and vedolizumab assessed in independent UC cohorts, including key registration trials. Results: Principal component analysis showed clear separation between control and experimental colitis samples, which clustered according to the specific model and classification, such as chemically induced (DSS and DNBS), T-cell dependent (T-cell transfer model and Il10-/ -, and T-cell independent, innate-mediated models (anti-CD40 mAb and TRUC models). Between 1700 and 8200 genes were differentially expressed (FDR < 0.05) between the experimental models and the corresponding controls; 145 genes had expression levels at least doubled up in all cases. Pathway analysis highlighted significant shared effects (FDR<0.05) on known cytokine-cytokine receptor interactions, signalling by interleukins and neutrophil degranulation. Genes expressed more specifically in the T-cell dependent models were enriched in immune processes such as the complement system, FCERI signalling and downstream activation of MAPK and NFKB, while those more specific to chemically-induced models were enriched in extracellular matrix functions like degradation and remodelling. A set of 21 genes involved in neutrophil degranulation, and over-expressed across all models of colitis, was also significantly enriched in the colon of patients with active UC. Moreover, the magnitude of enrichment of this gene list could differentiate between responders and non-responders to infliximab (difference in median -704.58, p=0.01) and ustekinumab (difference in median -771.08, p=2.19e-08) but not vedolizumab (difference in median 2212.71, p=0.37). Conclusion: This transcriptional atlas provides a new lens to scrutinize fundamental biological pathways of gut inflammation and new opportunities to understand the core molecular features of the resistome. A set of neutrophil degranulation genes was associated with resistance to anti-cytokine therapies in UC.